STUDI PERBANDINGAN ANTARA SISTEM KONTRAK LUMPSUM DAN KONTRAK UNIT PRICE (HARGA SATUAN)PADA PROYEK PEMBANGUNAN GEDUNG SMP N 6 SAMARINDA - SEPTI PERMATA SARI, WINDA (KURVA S JURNAL MAHASISWA, 2014)
The construction projectis a project thathas a lot ofuncertaintiesandrisks. Requiredarisk management approachto identify andcontrol the risksthat might occur. One of themost importantphaseofrisk managementisrisk analysisthat aims to identifysignificantrisksto the project.In this study,the riskanalysis will be doneona comparative studybetweenthe systemcontractsandcontractUnit PricePer diemson projectbuildingSmpN6Samarinda.